Formation of visual-figurative thinking on math lessons in 5 grades in case of the use of the software environment «1C: Math designer» - Kukhtinova, A.P. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
This article is devoted to the visual-figurative thinking on Math lessons with the use of information technologies. The great scholars’ views on the issue are being studied. The article shows how various electronic educational resources and pedagogical tools work. Features and opportunities of the use of visual methods on the base of the software environment “1C: Math designer” have been identified. The advantages of the computer program on Math lessons in 5 grades are being considered. They show the students’ high academic motivation in learning and its positive dynamics.